Sayyed Hossein Nasr’s Critique of Modernity: The Perspective of Perennial Philosophy and Its Relevance to Contemporary Islamic Thought - Al Maulud; Helmi Syaifuddin (An-Nida')
Modernity has not only resulted in advancements in science and technology but has also given rise to fundamental dilemmas within the landscape of contemporary Islamic thought—particularly concerning the crisis of meaning, the marginalization of spirituality, and the dominance of secular epistemology. This article aims to analyze Sayyed Hossein Nasr’s critique of modernity and examine the relevance of the perennial philosophy he proposes in addressing these challenges within the context of contemporary Islamic thought. This study employs a qualitative research method grounded in library research. The approach utilized is philosophical hermeneutics combined with discourse analysis of Nasr’s thought, particularly referencing primary works such as Islam and the Plight of Modern Man. Nasr contends that modernity is inherently reductionist, as it places excessive emphasis on the empirical-material dimension while neglecting the metaphysical aspect and the human connection to transcendent reality. In response, the perennial philosophy he advocates underscores the significance of universal spiritual values, the transcendent unity of religions, and the preservation of tradition as foundational elements for restoring the balance between spirituality and rationality in contemporary life. Unlike previous studies, this article specifically emphasizes the integration of Nasr’s perennial philosophy with the dynamics of contemporary Islamic thought, particularly in addressing the epistemological crisis resulting from the modernization of knowledge. The article contributes to the discourse on the significance of revitalizing spirituality and the Islamic scholarly tradition as a critical and constructive response to the dominance of modernity.